Evidence on Income Measurement Properties of ASR No. 190 and SFAS No. 33 Data - Haw, In-Mu; Lustgarten, Steven (Journal of Accounting Research, 1988)
Income measurement, Historical cost earnings, ASR No. 190, SFAS No. 33